2012
DOI: 10.1182/blood-2011-04-347518
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR4 with cell-penetrating pepducins in lymphoma and lymphocytic leukemia

Abstract: The chemokine receptor CXCR4, which normally regulates stromal stem cell interactions in the bone marrow, is highly expressed on a variety of malignant hematologic cells, including lymphoma and lymphocytic leukemias. A new treatment concept has arisen wherein CXCR4 may be an effective therapeutic target as an adjunct to treatment of hematologic neoplasms with chemo-and immunotherapy. In the present study, we developed pepducins, cell-penetrating lipopeptide antagonists of CXCR4, to interdict CXCL12-CXCR4 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 56 publications
2
44
0
2
Order By: Relevance
“…Moreover, antagonizing CXCR4 and CXCL12 significantly inhibited the growth of Epstein-Bar virus (EBV)-transformed B cells injected intraperitoneally into NOD/SCID mice and prolonged animal survival (39). Furthermore, recently published study has shown the efficacy of cell-penetrating lipopeptide CXCR4 antagonists, called pepducins, to enhance rituximab-induced apoptosis of lymphoma cells in vitro and in vivo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antagonizing CXCR4 and CXCL12 significantly inhibited the growth of Epstein-Bar virus (EBV)-transformed B cells injected intraperitoneally into NOD/SCID mice and prolonged animal survival (39). Furthermore, recently published study has shown the efficacy of cell-penetrating lipopeptide CXCR4 antagonists, called pepducins, to enhance rituximab-induced apoptosis of lymphoma cells in vitro and in vivo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mode of action is not completely understood, it is believed that pepducins bind to their target receptors and allosterically modulate their signaling activity (2,3). Pepducins have been identified for several GPCRs, including the proteaseactivated receptors PAR1 (1,(4)(5)(6)(7)(8)(9)(10), PAR2 (1,(11)(12)(13), and PAR4 (6,9), the formyl peptide receptor-2 (14), the melanocortin type 4 receptor (1), the sphingosine 1-phosphate receptor 3 (15), and the C-X-C chemokine receptor type 1, 2 (CXCR1, CXCR2) (16), and 4 (CXCR4) (2,17,18). They have been found to act as allosteric agonists as well as negative or positive allosteric modulators.…”
mentioning
confidence: 99%
“…Вследствие этого, селективные CXCR4-антагонисты, в том числе созданные на основе пепдуцинов, представляют большой интерес как противораковые препараты, действие которых основано на прерывании сигналов, генерируемых активацией рецептора CXCR4 [17,32]. Обнаружено, что пепдуцины, производные ЦП-1 и ЦП-3 рецептора CXCR4, полностью блокируют опосредуемую этим рецептором миграцию клеток лимфоцитарного лейкоза и лимфомы [33]. Несмотря на то, что проапоптотическое действие ретуксимаба, моноклональных антител к CD20-антигену, который экспрессируется в B-клетках лимфомы, полностью блокировалось обработкой этих клеток стромальным фактором CXCL12/SDF-1, при совместном действии ретуксимаба и CXCR4-пепдуцинов их проапоптотический эффект в присутствии фактора CXCL12/SDF-1 сохранялся.…”
Section: влияние на ангиогенез развитие злокачественных опухолей и мunclassified
“…Несмотря на то, что проапоптотическое действие ретуксимаба, моноклональных антител к CD20-антигену, который экспрессируется в B-клетках лимфомы, полностью блокировалось обработкой этих клеток стромальным фактором CXCL12/SDF-1, при совместном действии ретуксимаба и CXCR4-пепдуцинов их проапоптотический эффект в присутствии фактора CXCL12/SDF-1 сохранялся. Пепдуцины как при монотерапии, так и в сочетании с ретуксимабом, также эффективно подавляли развитие и метастазирование трансплантантов лимфомы и лимфоцитарного лейкоза [33].…”
Section: влияние на ангиогенез развитие злокачественных опухолей и мunclassified